Multiple Antigen Peptide Containing B and T Cell Epitopes of F1 Antigen of Yersinia pestis Showed Enhanced Th1 Immune Response in Murine Model. (23rd April 2013) - Ali, R.; Naqvi, R. A.; Kumar, S.; Bhat, A. A.; Rao, D. N.
Abstract Yersinia pestis is a facultative bacterium that can survive and proliferate inside host macrophages and cause bubonic, pneumonic and systemic infection. Apart from humoral response, cell‐mediated protection plays a major role in combating the disease. Fraction 1 capsular antigen (F1‐Ag) of Y. pestis has long been exploited as a vaccine candidate. In this study, F1‐multiple antigenic peptide (F1‐MAP or MAP)‐specific cell‐mediated and cytokine responses were studied in murine model. MAP consisting of three B and one T cell epitopes of F1‐antigen with one palmitoyl residue was synthesized using Fmoc chemistry. Mice were immunized with different formulations of MAP in poly DL‐lactide‐co‐glycolide (PLGA) microspheres. F1‐MAP with CpG oligodeoxynucleotide (CpG‐ODN) as an adjuvant showed enhanced in vitro T cell proliferation and Th1 (IL‐2, IFN‐γ and TNF‐α) and Th17 (IL‐17A) cytokine secretion. Similar formulation also showed significantly higher numbers of cytokine (IL‐2, IFN‐γ)‐secreting cells. Moreover, F1‐MAP with CpG formulation showed significantly high (P < 0.001) percentage of CD4+ IFN‐γ+ cells as compared to CD8+ IFN‐γ+ cells, and also more (CD4‐ IFN‐γ)+ cells secrete perforin and granzyme as compared to (CD8‐ IFN‐γ)+ showing Th1 response. Thus, the study highlights the importance of Th1 cytokine and existence of CD4+ and CD8+ immune response. This study proposes a new perspective for the development of vaccination strategies for Y. pestis that trigger T cell immune response.